A Qualitative Assessment of Small Business Formation and Entrepreneurship during the COVID- 19 pandemic - Jamil Paolo S. Francisco; Regina Yvette V. Romero; John Paul C. Flaminiano (International Journal of Small and Medium Enterprises and Business Sustainability, 2023)
Using data from in-depth interviews with owner-managers of small firms in the Philippines, we studied the entrepreneurial process experienced by nascent entrepreneurs in starting new businesses during the pandemic. We examined the effects of the developing pandemic crisis on both the nascent entrepreneur and the nascent enterprise. We found that most entrepreneurs were driven by the necessity to find alternative sources of income during the pandemic. Two common features identified among pandemic startup entrepreneurs were the ability to recognize new market opportunities quickly and use bricolage to begin the entrepreneurial process despite resource constraints. We also found that online social capital built mainly on social media platforms played an important role in the process as mobility restrictions hampered traditional offline social networks.